Effect of aspirin resistance with dyslipidemia against VerifyNOW® measurement in Bethesda hospital Yogyakarta - Hardi astuti witasari; Rizaldy Taslim Pinzon; Erna Kristin (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: Aspirin is first line drug of choice to prevent ischemic stroke. However, some cases are found occuring of aspirin resistance. Objective: This study was to examine the effect of dyslipidemia on the risk of antiplatelet resistance with VerifyNOW ® at Bethesda Hospital Yogyakarta. Method: This research was observational analysis using a nested casecontrol study design. The subjects were ischemic stroke patients who underwent tests of platelet function by VerifyNOW® (Accumetrics, San Diego, CA, USA). The Case group was ischemic stroke patients who has history of aspirin resistance. The control group was ischemic stroke patients who response on aspirin therapy. Both groups were analyzed and compared to the state of dyslipidemia. Results: Bivariate analysis on the incidence of aspirin resistance indicate that dyslipidemia had OR = 0.979 (95% CI; 0.378 to 2.531), p = 0.572. Hypercholesterolemia had OR = 0,909 (CI 95%; 0,377-2,190) p = 0,500; hypertrigliceride had OR = 0,838 (CI 95%; 0,331-2,119) p = 0,409; abnormal HDL had OR = 1,468 (CI 95% 0,564-3,817) p = 0,238; abnormal LDL had OR = 0,937 (CI 95% 0,374-2,345) p = 0,500. Patient factors such as age >55 years (p = 0.168) and female gender (p = 0.226) showed a nonsignificant results. Conclusion: Ischemic stroke patients at Bethesda Hospital Yogyakarta who had dyslipidemia were not evident to have a greater risk of aspirin resistance than ischemic stroke patients who did not undergo dyslipidemia.